Direct syngas hydrogenation over a Co–Ni bimetallic catalyst: Process parameter optimization. (2nd October 2015) - Ramasamy, Karthikeyan K.; Gray, Michel; Job, Heather; Wang, Yong
Abstract: The syngas hydrogenation activity of the Co–Ni bimetallic catalyst containing total metal loading less than 10 wt% was prepared via a wet impregnation method and was studied with respect to the reaction temperature and the catalyst composition. Among the hydrocarbons generated, small olefinic compounds between C2 and C7 (up to 40%) were the highest in the product mixture. The olefin to paraffin ratio for C3 hydrocarbon is around 8. For all variables tested, the product distribution contains up to 10% oxygenates along with the hydrocarbon compounds. An acidic alumina containing reactor was added followed by the Co–Ni containing reactor to demonstrate the deoxygenation of oxygenates generated from the FTS process to improve the small olefinic fraction and the overall carbon yield to the valuable products. Highlights: Low metal loading Co–Ni bimetallic catalyst for the CO hydrogenation/FTS. Very high olefin to paraffin ratio generated. The highest olefin to paraffin ratio of 8 was observed for C3 hydrocarbon. Demonstrated dual bed configuration to convert oxygenates.